Identification of Geothermal Reservoirs in South Cameroon from a Combined Landsat 8 and AMT Data - Piameu Kwagag Joel; Owona Angue Marie Louise-Clotilde; Ngatchou Evariste; Njingti Nfor; Kue Petou Rokis Malquaire; Njandjock Nouck Philippe (International Journal of Geophysics)
This geothermal source prospecting work is carried out in order to respond to the energy deficit affecting the populations of South Cameroon in particular. The study combines audio-magnetotelluric (AMT) and Landsat 8 data for the geolocation of reservoirs, as well as the geological and tectonic information. The processing of these data defined 5 profiles and led to two-dimensional models of resistivity sections for each profile. The interpretation of the data identified a highly conductive zone with a resistivity ranged 1–10 Ω·m at an estimated depth of 1200 m in the locality of Menve’ele. The Landsat 8 data collected in this area during the same period enabled the elaboration of temperature and lineament anomaly maps of the study area. High-temperature areas with high lineament predominance correlate better with areas of low resistivity. For example, Menve’ele (A1) has a surface temperature range of 20°C–30°C and a high density of lineaments. By correlating these results with those provided by previous authors, the Menve’ele locality may be the target of a potential geothermal reservoir. A 3D resistivity model is built to better understand the variations of resistivity and their depths. The geological and tectonic information of the region confirm the tectonic origin of the faults and lineaments as well as the predominance of metamorphic and sedimentary formations.